Paderborner Qualitätsstern (PQ³) zur Einschätzung der Kooperation im Übergang Kita – Grundschule: ein Selbstevaluationsinstrument für multiprofessionelle und institutionsübergreifende Zusammenarbeit - Herding, Jana; Höke, J.; Büker, P.; Ogrodowski, J. (Diskurs Kindheits- und Jugendforschung/Discourse. Journal of Childhood and Adolescence Research)

Paderborner Qualitätsstern (PQ³): Self-evaluation of transition to school programms for educators and teachers - Herding, Jana; Büker, P.; Höke, J.; Ogrodowski, J. (Evaluation Transition to School Programms: Learning from Research and Practice)

KrafT Bildungsdokumentation: Kind- und ressourcenorientierte, analysebasierte, fortschrittsorientierte Bildungsbegleitung im Team planen, dokumentieren und reflektieren. Herausgegeben von: Büker, Petra; Ogrodowski, Jana, und Antenbrink, Teresa - Herding, Jana

Corona und Krise. Perspektiven erziehungswissenschaftlicher Frauen- und Geschlechterforschung - Mattei, Annalisa; Eremin, Oxana (Bericht zur Jahrestagung der Sektion Frauen- und Geschlechterforschung in der Erziehungswissenschaft in der Deutschen Gesellschaft für Erziehungswissenschaft)

Rezension zu: Nef, Susanne: Ringen um Bedeutung. Die Deutung häuslicher Gewalt als sozialer Prozess, Basel 2020, in: Fegter, Susann / Langer, Antje / Thon, Christine (Hgg.): Diskursanalytische Geschlechterforschung in der Erziehungswissenschaft - Mattei, Annalisa (Jahrbuch Erziehungswissenschaftliche Geschlechterforschung 17, Opladen / Berlin / Toronto)

Jahrestagung „Corona und Krise – Perspektiven erziehungswissenschaftlicher Frauen- und Geschlechterforschung“ Erziehungswissenschaft Heft 63, Jg. 32|2021 - Mattei, Annalisa; Eremin, Oxana

Entwicklungschance oder Warteschleife? Berufsorientierung und Berufswahl in der Berufsfachschule - Schemmer, Susanne Jutta; Heisler, Dietmar; Rink, Julia (Entwicklungen und Perspektiven in der Berufsorientierung. Stand und Herausforderungen. Online: (06.12.2021))

Carbon Dating of Seven Parchment Qurʾān Manuscripts and One Syriac Bible of the National Museum of Iran - Aghaei Abrandabadi, Seyed Ali; Marx, Michael (Journal of Iranian National Museum, 2)

David und Salomon im Koran: ein Komparativ-theologischer Ansatz - Saad, Nadia (Erlanger Jahrbuch für Interreligiöse Diskurse. Methoden der Darstellung und Analyse interreligiöser Diskurse)

I-AID: Identifying Actionable Information From Disaster-Related Tweets - Zahera, H.M.A; Jalota, Rricha; Sherif, Mohamed Ahmed; Ngomo, Axel-Cyrille Ngonga (IEEE Access)
Keywords: General Engineering; General Materials Science; General Computer Science

ASSET: A Semi-supervised Approach for Entity Typing in Knowledge Graphs - Zahera, H.M.A; Heindorf, Stefan; Ngomo, Axel-Cyrille Ngonga (Proceedings of the 11th on Knowledge Capture Conference)

Essays on Modeling Languages and Software Tools for Business Model Innovation: Theory and Empirical Evidence - Szopinski, Daniel

Decomposition-Guided Reductions for Argumentation and Treewidth - Fichte, Johannes; Hecher, Markus; Mahmood, Yasir; Meier, Arne (Proceedings of the Thirtieth International Joint Conference on Artificial Intelligence)
Argumentation is a widely applied framework for modeling and evaluating arguments and its reasoning with various applications. Popular frameworks are abstract argumentation (Dung’s framework) or logic-based argumentation (Besnard-Hunter’s framework). Their computational complexity has been studied quite in-depth. Incorporating treewidth into the complexity analysis is particularly interesting, as solvers oftentimes employ SAT-based solvers, which can solve instances of low treewidth fast. In this paper, we address whether one can design reductions from argumentation problems to SAT-problems while linearly preserving the treewidth, which results in decomposition-guided (DG) reductions. It turns out that the linear treewidth overhead caused by our DG reductions, cannot be significantly improved under reasonable assumptions. Finally, we consider logic-based argumentation and establish new upper bounds using DG reductions and lower bounds.

Parameterised complexity of model checking and satisfiability in propositional dependence logic - Mahmood, Yasir; Meier, Arne (Annals of Mathematics and Artificial Intelligence)
Abstract Dependence Logic was introduced by Jouko Väänänen in 2007. We study a propositional variant of this logic (PDL) and investigate a variety of parameterisations with respect to central decision problems. The model checking problem (MC) of PDL is NP -complete (Ebbing and Lohmann, SOFSEM 2012). The subject of this research is to identify a list of parameterisations (formula-size, formula-depth, treewidth, team-size, number of variables) under which MC becomes fixed-parameter tractable. Furthermore, we show that the number of disjunctions or the arity of dependence atoms (dep-arity) as a parameter both yield a paraNP-completeness result. Then, we consider the satisfiability problem (SAT) which classically is known to be NP -complete as well (Lohmann and Vollmer, Studia Logica 2013). There we are presenting a different picture: under team-size, or dep-arity SAT is paraNP -complete whereas under all other mentioned parameters the problem is FPT . Finally, we introduce a variant of the satisfiability problem, asking for a team of a given size, and show for this problem an almost complete picture.
Keywords: Applied Mathematics; Artificial Intelligence

A Parameterized View on the Complexity of Dependence Logic - Kontinen, Juha; Meier, Arne; Mahmood, Yasir (Logical Foundations of Computer Science)

Dynamic Monopolistic Competition - Hoof, Simon (Journal of Optimization Theory and Applications)
I study a dynamic variant of the DixitâStiglitz (Am Econ Rev 67(3), 1977) model of monopolistic competition by introducing price stickiness Ã  la Fershtman and Kamien (Econometrica 55(5), 1987). The analysis is restricted to bounded quantity and price paths that fulfill the necessary conditions for an open-loop Nash equilibrium. I show that there exists a symmetric steady state and that its stability depends on the degree of product differentiation. When moving from complements to perfect substitutes, the steady state is either a locally asymptotically unstable (spiral) source, a stable (spiral) sink or a saddle point. I further apply the Hopf bifurcation theorem and prove the existence of limit cycles, when passing from a stable to an unstable steady state. Lastly, I provide a numerical example and show that there exists a stable limit cycle.

Accounting for Heuristics in Reputation Systems: An Interdisciplinary Approach on Aggregation Processes - van Straaten, Dirk; Melnikov, Vitalik; Hüllermeier, Eyke; Mir Djawadi, Behnud; Fahr, René
Aggregation metrics in reputation systems are important for overcoming information overload. When using these metrics, technical aggregation functions such as the arithmetic mean are implemented to measure the valence of product ratings. However, it is unclear whether the implemented aggregation functions match the inherent aggregation patterns of customers. In our experiment, we elicit customers' aggregation heuristics and contrast these with reference functions. Our findings indicate that, overall, the arithmetic mean performs best in comparison with other aggregation functions. However, our analysis on an individual level reveals heterogeneous aggregation patterns. Major clusters exhibit a binary bias (i.e., an over-weighting of moderate ratings and under-weighting of extreme ratings) in combination with the arithmetic mean. Minor clusters focus on 1-star ratings or negative (i.e., 1-star and 2-star) ratings. Thereby, inherent aggregation patterns are neither affected by variation of provided information nor by individual characteristics such as experience, risk attitudes, or demographics.

Incentive Schemes in Customer Rating Systems - Comparing the Effects of Unconditional and Conditional Rebates on Intrinsic Motivation - van Straaten, Dirk

Fighting Fire with Fire - Overcoming Ambiguity Aversion by Introducing more Ambiguity - van Straaten, Dirk; Fahr, René

Political Speaker Transfer: Learning to Generate Text in the Styles of Barack Obama and Donald Trump - Bülling, Jonas